Momentum-topology-induced optical pulling force - Li, Hang (2020)
We report an ingenious mechanism to obtain robust optical pulling force by a single plane wave via engineering the topology of light momentum in the background. The underlying physics is found to be the topological transition of the light momentum from a usual convex shape to a starlike concave shape in the carefully designed background, such as a photonic crystal structure. The principle and results reported here shed insightful concepts concerning optical pulling, and pave the way for a new class of advanced optical manipulation technique, with potential applications of drug delivery and cell sorting.